A double blind lipase for lipase comparison of a high lipase and standard pancreatic enzyme preparation in cystic fibrosis. Issue 2 (February 1993) - Bowler, I M; Wolfe, S P; Owens, H M; Sheldon, T A; Littlewood, J M; Walters, M P
Abstract : A standard acid resistant microsphere pancreatic enzyme preparation was compared with identical capsules half filled with mini-tablets of a new high lipase preparation in a randomised double blind crossover study in children with cystic fibrosis. Each patient received his/her usual number of capsules and the same dose of lipase during each period of the study. Eighteen patients completed the study. There were fewer gastrointestinal symptoms when pancreatic enzyme was supplied as the high lipase preparation. There was also a significant improvement in fat absorption (17%, 95% confidence interval (CI) 6 to 27), reduction in faecal fat output (15.8 g/day, 95% CI 6.4 to 22.5), and faecal energy loss (789 kJ/day, 95% CI 211 to 1384). It is concluded that half filled capsules of the new high lipase preparation are more effective than the standard preparation and it is likely that filled capsules would allow patients to use fewer than half the number of pancreatic enzyme capsules.